2008
DOI: 10.2136/sssaj2006.0281
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy and Magnetic Properties of Basaltic Substrate Soils: Kaho'olawe and Big Island, Hawaii

Abstract: Magnetic behavior of soils can seriously hamper the performance of geophysical sensors. Currently, we have little understanding of the types of minerals responsible for the magnetic behavior, as well as their distribution in space and evolution through time. This study investigated the magnetic characteristics and mineralogy of Fe‐rich soils developed on basaltic substrate in Hawaii. We measured the spatial distribution of magnetic susceptibility (χlf) and frequency dependence (χfd%) across three test areas in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 24 publications
1
16
0
1
Order By: Relevance
“…Detailed studies on the potential pathways for this magnetic enhancement were carried out by Maher and Taylor (1988), Fassbinder and Stanjek (1993), Kletetschka and Banerjee (1995) and Liu et al (2004). Many investigations focused on the rock magnetic properties of soil profiles developed on basaltic (Van Dam et al, 2008) and calcareous (Lu et al, 2012) rocks and loess-paleosol sequences (Han et al, 1996;Maher and Thompson, 1991). Soil magnetic studies were carried out to determine the relationship between magnetic properties and parent rock lithology (Fialova et al, 2006;Maher, 1986;Shenggao, 2000), heavy metal and fly-ash pollution (Kapicka et al, 2000;Wang, 2013), archaeology (Jeng et al, 2003) and paleoclimate (Geiss et al, 2008;Maher et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed studies on the potential pathways for this magnetic enhancement were carried out by Maher and Taylor (1988), Fassbinder and Stanjek (1993), Kletetschka and Banerjee (1995) and Liu et al (2004). Many investigations focused on the rock magnetic properties of soil profiles developed on basaltic (Van Dam et al, 2008) and calcareous (Lu et al, 2012) rocks and loess-paleosol sequences (Han et al, 1996;Maher and Thompson, 1991). Soil magnetic studies were carried out to determine the relationship between magnetic properties and parent rock lithology (Fialova et al, 2006;Maher, 1986;Shenggao, 2000), heavy metal and fly-ash pollution (Kapicka et al, 2000;Wang, 2013), archaeology (Jeng et al, 2003) and paleoclimate (Geiss et al, 2008;Maher et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic enhancement in the topsoils is mostly due to the increased concentrations of pedogenic magnetite and maghemite. The pedogenesis of magnetic minerals can be explained by several models, namely: fire-induced transformation of weak magnetic iron oxides and hydroxides in the presence of organic matter; long-term weathering of residual primary magnetite and biotic formation by bacteria (Blundell et al, 2009;Dearing et al, 1997Dearing et al, , 2001Fassbinder et al, 1990;Guyodo et al, 2006;Liu et al, 2010aLiu et al, , 2010bLiu et al, , 2010cLu, 2003;Lu et al, 2008;Maher and Taylor, 1988;Torrent et al, 2010a,b;Van Dam et al, 2008). However, only a few publications have been devoted to highly magnetic soils in the subtropical and tropical regions.…”
Section: Introductionmentioning
confidence: 99%
“…Soil magnetic measurements also indicated that the highly magnetic soils were commonly found in the basaltic parent materials of subtropical and tropical regions (da Costa et al, 1999;Lu et al, 2008;Moukarika et al, 1991;Paduani et al, 2009;Resende et al, 1986;Taylor and Schwertmann, 1974;Van Dam et al, 2008). These highly magnetic soils may produce magnetic anomalies similar to those characteristics of anthropogenic objects, such as buried waste drums, and seriously hamper the performance of geophysical sensors and interpretation of airborne geophysical surveys (Rivers et al, 2004;Van Dam et al, 2008). However, the highly magnetic soils are also commonly formed on non-magnetic limestone parent materials in hot subtropical climates with alternating wet and dry seasons.…”
Section: Introductionmentioning
confidence: 99%
“…This interpretation is consistent with previously reported analytical data (Cador et al 2008). Out of these minerals, KFeO 2 has been known to be antiferromagnetic with Néel temperature 960 K (Tomkowicz and Szytuła 1977) and CaCO 3 , KCl, and SiO 2 are diamagnetic (Moon et al 2006;Van Dam et al 2008). It is interesting to note that the ashes, obtained from all four branded cigarettes, contain identical chemical components but with very small variations in amounts.…”
Section: Resultsmentioning
confidence: 99%